RARE-30. PEDIATRIC GLIOBLASTOMA IN THE POST-TEMOZOLOMIDE ERA: OUTCOMES AND CHARACTERISTICS. (11th November 2019) - Chandra, Ankush; Oh, Taemin; Wadhwa, Harsh; Shah, Sumedh; Gupta, Nalin; McDermott, Mike; Berger, Mitchel; Aghi, Manish
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most common brain tumor, however, is a rare occurrence in children and is poorly characterized. We evaluated the characteristics and outcomes of pediatric GBM (pGBM). METHODS: Retrospective analysis of pediatric (age< 18) patients diagnosed with GBM undergoing first glioblastoma resection at our brain tumor center (2005- 2016). RESULTS: From 1457 GBM patients, we identified twenty-four (1.65%) pGBMs (Median Age=9 years, Females=45.8%). Median overall survival (OS) was 32.1 months, while the median progression-free survival was 11.5 months. The commonest symptoms at presentation were headaches (54.2%, n=13) and motor symptoms (50%, n=12). Mean tumor diameter was 4.5 cm and 25% of the cohort underwent gross total resection (GTR) of their tumor. Univariate analysis revealed median OS significantly associated with tumor extent of resection (GTR=56.4 months; STR/Biopsy=13.7 months, p=0.001), age at surgery (>10 years=43.9 months, < 10 years= 17.2 months, p=0.01), tumor size (> 4cm= 9.1 months, < 4cm=56.9 months, p=0.01), motor symptoms at presentation (present=14.9 months, absent=41.04 months, p=0.02) and infratentorial tumors (infratentorial=17.4 vs supratentorial=53.4 months, p=0.02). Multivariate analysis revealed GTR (HR 0.2[95% CI 0.07–0.72]; p=0.03), Age >10 years (HR 0.6[95% CI 0.02–0.64]; p=0.002), tumor >4 cm (HR 2.89[95% CI 1.88–4.11]; p=0.001) and EGFR amplification (HR 3.48[95% CI 0.82–17.4]; p=0.005) to be independent predictors of OS. Comparing patients under and over 10 years, we found that older patients had smaller tumors at presentation (4.9 vs 3.6 cms, p=0.03), greater rates of preoperative temozolomide (n=1, 7.7% vs n=6, 54.5%) and bevacizumab (n=1, 7.7% vs n=4, 36.4%) treatment, and lower rates of EGFR amplification (66.7% vs 11.1%) that could explain survival disparities between groups. CONCLUSION: Motor symptoms, larger tumors at presentation and tumor EGFR amplification may be indictive of poorer outcomes in pGBM. However, maximal tumor resection, aggressive chemoradiation and tumor presentation at age >10 years may confer better prognosis in these patients.